F‐18‐FDG PET‐CT in children and young adults with Ewing sarcoma diagnosed in Norway during 2005–2012: a national population‐based study. (3rd June 2015) - Johnsen, Boel; Boye, Kjetil; Rosendahl, Karen; Biermann, Martin; Trovik, Clement; Aukland, Stein Magnus
Summary: Background: To examine national imaging strategies regarding the use of F‐18‐FDG PET‐CT in patients with Ewing sarcoma and study factors that might influence the use of PET‐CT, such as tumour biology (Picci grade of operation specimen), clinical disease stage and age. Methods: We examined the medical records including pathology and imaging of all patients below 30 years diagnosed with Ewing sarcoma in Norway in 2005–2012. Results: Of 61 patients treated at one of the two national sarcoma treatment service centres (Oslo: 35, Bergen: 26), 29 patients had localized disease, 8 had tumour extending to organs nearby and 24 had metastases. Among 35 operated patients with neoadjuvant chemotherapy, 15 had Picci grades II and III ( good responders ) and 20 grade I ( poor responders ). We found a significant difference in the use of PET‐CT (Oslo/Bergen 0·9 versus 2·0 scans per patient, P = 0·010) and in the use of MRI (Oslo/Bergen: eight versus 13, P = 0·006). No differences were proven for ultrasound, radiography, CT or skeletal scintigraphy. The number of PET‐CTs was associated with clinical disease stage at diagnosis ( P = 0·041) but not with Picci grade or age. The number of PET studies was not correlated to the number of MR studies. Conclusions: The use of PET‐CT in children and young adults diagnosed with Ewing sarcoma in Norway during 2005–2012 at the two national sarcoma treatment service centres differed significantly. The use of PET‐CT imaging was related to the clinical disease stage at diagnosis but unrelated to patient age and tumour biology (Picci grade).